Mechanism of MutLβ-dependent DNA expansions - Lyudmila Y. Kadyrova; Farid F. Kadyrov; Bruce Hayward; Karen Usdin; Farid A. Kadyrov (Proceedings of the National Academy of Sciences, 2026)
MutS and MutL proteins and their eukaryotic homologs have important functions in DNA metabolism. MutLβ (MLH1-PMS1 heterodimer) is a poorly understood eukaryotic MutL complex. Recent genetic studies have implicated MutLβ in the process of expansion of the short, tandem DNA repeat tracts that is responsible for the repeat expansion diseases. The function of MutLβ and the mechanism of MutLβ-dependent DNA expansions have not been established. We show here that MutLβ promotes MutSβ- and MutLγ-dependent DNA expansions in human cell extracts and defined systems. Importantly, DNA expansions that occur in human cell extracts in the presence of MutSβ and a low concentration of MutLγ require MutLβ. A MutSβ variant lacking the PCNA-binding motif is proficient in supporting MutLβ-promoted and MutLγ-dependent DNA expansions. We also show that MutLβ enhances the MutSβ-dependent endonuclease activity of MutLγ that incises the loop-lacking strand of loop-containing DNAs. MutLβ also increases the endonuclease activity of MutLγ in the presence of ATP-Mn 2+ and physically interacts with MutLγ, MutSβ, and PCNA. In addition, MutLβ suppresses inhibition of DNA expansion by MutSα. An MLH1-F80V substitution in MutLβ causes a defect in the ability of the protein to promote MutSβ- and MutLγ-dependent DNA expansions. Taken together, our findings support a model in which MutLβ is involved in DNA expansions by acting in a MutSβ- and MutLγ-dependent mechanism that includes incision of loop-containing DNAs in the loop-lacking strand.